Role of social capital in international financial integration, economic growth, and financial development - Shad, Maryam (2018)
This study incorporates four components such as social trust, norms, network, and social structure to construct social capital series, to investigate the effect of social factors on variation of international financial integration (IFI), economic growth, and financial development from 1990-2014. This investigation is three essays. The first essay investigates the impact of social capital on IFI. The second essay examines the impact of human capital on social capital-growth nexus. The third essay investigates the influence of social capital on financial development. This thesis discusses each essay in a different chapter. In the first essay, the impact of social capital on IFI is investigated. Many studies illustrate that the interest for increasing IFI is due to motivation to benefit from higher rate of return and find more opportunity for risk diversification. This reason induce policy makers to implement policies that can help improve financial market cooperation among countries. Despite the similarity in financial policy implemented by countries, the results are different in terms of the level of integration and risk adjustments. This essay try to investigate why some countries are more financially integrated than the other countries. The social capital is identified as one of the perquisites of IFI. Although the literature claims that social capital can facilitate IFI, the relationship between social capital and IFI is inconclusive. In order to examine the relationship between these two variables, this study employs generalized method of moment (GMM) panel as a regression technique by using the sample of 60 countries in the 1990-2014 periods. The results suggest that social capital can positively affect IFI. This is consistent with the view of literatures that suggest that IFI needs informal institution arrangements such as trustworthiness, controls of internal management, ethical infrastructure and the quality of collateral. Therefore, policymakers should weigh the cost of policies aimed at reinforcing social factors in addition to improve formal institution. Second essay evaluates the role of human capital in mediating the effect of social capital on economic growth. Empirical studies show that the role of social capital in economic growth is inconclusive. This linkage suggests that the impact of social capital on economic growth is perhaps conditional on the effect of other variables. The hypothesis is tested employing sample of 68 countries for the 1990-2014 period. Using GMM panel estimator, the results indicate that social capital has no direct effect on economic growth. However, social capital interaction with human capital (education) is found to be important for economic growth. This suggests that the marginal impact of social capital on growth is increasing in the level of education such that countries with higher level of education will benefit from lower transaction costs and hence higher productivity level. In third essay, this study investigates the role of social capital in the financial development. Many countries try to develop their financial market and create more stable economic environment. Thus, people can borrow greater amounts at cheaper rates and can invest in a multitude of instruments and share risks with strangers from across the globe. The beneficiary impacts of financial development induce policy makers to investigate the precise initiatives that can promote financial development in countries. Therefore, numerous studies try to find the factors effecting financial development. Despite the attempt of countries to remove the obstacles to promote their financial development, the level of development in financial market is varied. Some studies suggest that differences in cross-country financial development can be related to other factors than formal institutions that is called informal institutions. This study aims to examine the link between social capital and financial development using GMM panel estimator for the sample of 60 countries from 1990 to 2014. Financial development incorporates contracts, warranties, and legal advices, which are categorized as transaction costs. Theoretically, social capital can reduce transaction costs which may enhance and facilitate movements of capital (Guiso et al., 2000). The findings suggest that social capital has positive impact on the financial development. The results support the idea that informal institutions are important in development of financial market. In another word, social factors can promote enforceability of formal contract that could promote financial development.